Comparative evaluation of bovine pericardial membrane and amniotic membrane in wounds skin healing in rabbits: N.H. Al-Falahi¹; Dhyaa. Ab. Abood² and M.S. Dauood2 - Al-Falahi, N. H. (The Iraqi Journal of Veterinary Medicine, 2018)
The present study aimed to compare between the amniotic and pericardial membranes for the wound dressing models. Ten local breed rabbits have been used in the current study. They were divided into two main equal groups: Experiment (Amniotic and pericardial membranes) and control group. According to healing periods each group was subdivided into four subgroups (7, 14, 21 and 28) days post wounding. Specimens of amniotic membranes were collected from full term pregnant cows, and pericardium was obtained from abattoir immediately after slaughtering. The study was conducted on skin wound for experiment application site as full-thickness skin wounds (3×3 cm) were done on the dorsal thoracic sides. Histopathological evaluation of study depended on the degrees of inflammatory exudate, epithelialization, fibroplasia and type of leukocytes infiltration. Results revealed marked reduction of the inflammatory phase during all periods of post treatment with amniotic membrane, the degree of epithelization and fibroplasia in addition to angiogenesis were enhanced in amniotic and pericardial dressed wounds during period of 14 and 21 days. The study concluded that no significant differences are between the pericardial membrane and of amniotic membrane in wound healing of skin.